2007
DOI: 10.1002/asia.200600385
|View full text |Cite
|
Sign up to set email alerts
|

Folding Dynamics of 10‐Residue β‐Hairpin Peptide Chignolin

Abstract: Short peptides that fold into beta-hairpins are ideal model systems for investigating the mechanism of protein folding because their folding process shows dynamics typical of proteins. We performed folding, unfolding, and refolding molecular dynamics simulations (total of 2.7 micros) of the 10-residue beta-hairpin peptide chignolin, which is the smallest beta-hairpin structure known to be stable in solution. Our results revealed the folding mechanism of chignolin, which comprises three steps. First, the foldin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
85
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 49 publications
7
85
0
Order By: Relevance
“…In conventional MD simulation, the first folding was observed at 0.4 μs starting from an extended conformation. 24 In distinct 1.6 and 1.8 μs conventional MD simulations, two folding events were observed at 450 ns and 1.2 μs in the former but no folding event was observed in the latter. 59 It was also reported that folding takes ∼50 ns in the replica exchange MD.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conventional MD simulation, the first folding was observed at 0.4 μs starting from an extended conformation. 24 In distinct 1.6 and 1.8 μs conventional MD simulations, two folding events were observed at 450 ns and 1.2 μs in the former but no folding event was observed in the latter. 59 It was also reported that folding takes ∼50 ns in the replica exchange MD.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…2(a)) in micro second order by all-atom (AA) MD simulations in explicit solvent. [23][24][25][26] As the reactant, extended structure was modeled using the AMBER leap module. 27 As the product, the final structure of 1-ns MD simulation in explicit water starting from the NMR structure (Model #1 in the PDB entry 1UAO) 22 was employed.…”
Section: B Simulated Systemsmentioning
confidence: 99%
“…For this reason, miniproteins such as the chignolin peptide [16] have been designed for use as folding models and have been a useful tool for folding studies involving long MD simulations [17][18][19]. Chignolin is a good folding model because it is constituted by only 10 residues (GYDPETGTWG) and because its tertiary structure folded in water is unique [16].…”
Section: Introductionmentioning
confidence: 99%
“…Using two peptides as examples we show that the deviations in the folding times can reach an order of magnitude for modest variations of the molecular model. We, therefore, conclude that the folding rate values obtained in molecular dynamics simulations have to be treated with care.Modern computational power is enough to simulate small proteins up to the times when they fold into their native conformations [1][2][3][4]. This is a remarkable achievement because phenomenological, relatively simple interatomic interactions built into the model lead to the molecular structures that essentially coincide with the crystallographically determined native conformations.…”
mentioning
confidence: 99%
“…Modern computational power is enough to simulate small proteins up to the times when they fold into their native conformations [1][2][3][4]. This is a remarkable achievement because phenomenological, relatively simple interatomic interactions built into the model lead to the molecular structures that essentially coincide with the crystallographically determined native conformations.…”
mentioning
confidence: 99%